2009
DOI: 10.1016/j.cellimm.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol exhibits specificity in its effects on differentiation of hematopoietic progenitors

Abstract: Ethanol is a known teratogen but the mechanisms by which this simple compound affects fetal development remain unresolved. The goal of the current study was to determine the mechanism by which ethanol affects lymphoid differentiation using an in vitro model of ethanol exposure. Primitive hematopoietic oligoclonal neonatal progenitor cells (ONP), with the phenotype Lin − HSA lo CD43 lo Sca-1 − c-Kit + that are present in neonatal but not adult bone marrow were sorted from the bone marrow of 2-week-old C57BL/6J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…However, given their location within the genes, it is possible that all three of these polymorphisms may alter mRNA expression levels. The rs1150226 is located in the promoter region of HTR3A within 1 kb of putative binding sites for several transcription factors that have been shown to be modulated by ethanol (41, 42). Furthermore, genetic association analyses have shown an association of rs1150226 with alcoholism comorbid with antisocial personality disorder (16), altered temporal lobe activity (43), and clozapine treatment outcome for schizophrenia (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, given their location within the genes, it is possible that all three of these polymorphisms may alter mRNA expression levels. The rs1150226 is located in the promoter region of HTR3A within 1 kb of putative binding sites for several transcription factors that have been shown to be modulated by ethanol (41, 42). Furthermore, genetic association analyses have shown an association of rs1150226 with alcoholism comorbid with antisocial personality disorder (16), altered temporal lobe activity (43), and clozapine treatment outcome for schizophrenia (44).…”
Section: Discussionmentioning
confidence: 99%
“…Our examination of CLPs showed a robust increase in the frequency of these progenitors in the alcohol-administered animals after 3 months. Studies in mice have demonstrated that in vitro alcohol can inhibit B cell differentiation at the stage of the CLP (Wang et al, 2009). Our results suggest that the CLP differentiation is inhibited by alcohol administration, leading to an accumulation of this progenitor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that alcohol can affect the ONP cell differentiation into a B lineage both in vitro and in vivo (Wang et al, 2006(Wang et al, , 2009. However, it is important to know; (a) whether alcohol affects cell differentiation at an early stage, late stage or on both stages, (b) does the effect of alcohol on B-cell differentiation temporary or permanent and (c) the mechanism by which alcohol affects the progenitor B-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…TFs activate or repress target genes and signaling receptors induce or modify the activities of gene regulatory proteins. Previous studies in this laboratory showed that ONP cells sorted from alcohol-exposed animals failed to up-regulate IL-7Rα and had decreased expression levels of down-stream EBF and Pax5 during in vitro culture under conditions that favored differentiation to the B lineage (Wang et al, 2009). This indicated the impaired commitment of progenitors to the B lineage.…”
Section: Introductionmentioning
confidence: 88%